A Social Movement Identity Instrument for Integrating Survey Methods Into Social Movements Research. (May 2017) - Allen, Summer; McCright, Aaron M.; Dietz, Thomas
Given increasing scholarly recognition of the need to better understand the factors that influence identification with or participation in social movements, we build upon recent work that integrates public opinion methods and analytical techniques into social movements research. Specifically, we revise an existing measure of environmental movement identity into a general measure of identification with a broad range of movements. Our analyses show that this new instrument captures meaningful variation across levels of identification with 20 major U.S. social movements and also helps distinguish among three movement identity clusters that largely align with key movement families. Furthermore, we provide strong evidence that our instrument has construct validity, as selected predictors explain variation in the three movement identity clusters in ways expected by previous research. We close by proposing an agenda for future research that helps advance our understanding of public support for or engagement with social movements.